Financial incentives of subregional RAWP. Issue 6602 (3rd October 1987) - Bevan, G; Brazier, J
Abstract : Accounting for the cross boundary flows of residents from one health authority treated by another has been considered by the review of the Resource Allocation Working Party (RAWP) formula by the National Health Service Management Board. A common concern is that the approximate costs used are unfair to those authorities (typically those with teaching hospitals) that are likely to treat more complex cases. This paper argues that when spending exceeds the target allowance for acute services this is more likely to be due to district residents using services at a high rate than to inadequate compensation for inflows. Districts where residents make a high use of services are often those where there are large flows across district boundaries. Since authorities cannot control outflows there is little they can do to reduce their residents' high use of services. Furthermore, curious financial incentives can be inferred for clinicians in these districts if they were to take effective action to bring their district's spending to target levels. These problems are discussed to illuminate problems of accounting for cross boundary flows that alternatives to current practice must resolve.